2011
DOI: 10.1089/adt.2010.0327
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Flexible Cell-Based Assay for the Evaluation of Heat Shock Protein 70 Expression Modulators

Abstract: Heat shock protein 70 (Hsp70) is a chaperone protein that helps protect against cellular stress, a function that may be co-opted to fight human diseases. In particular, the upregulation of Hsp70 can suppress the neurotoxicity of misfolded proteins, suggesting possible therapeutic strategies in neurodegenerative diseases. Alternatively, in cancer cells where high levels of Hsp70 inhibit both intrinsic and extrinsic apoptotic pathways, a reduction in Hsp70 levels may induce apoptosis. To evaluate and identify, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Camptothecin is a well-characterized apoptosis inducing agent and often used as positive control [ 43 , 44 ]. Furthermore, heat shock treatment is a widely-used control method since eukaryotic cells form misfolded or aggregated proteins in the presence of thermal insults, thus inducing apoptosis [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Camptothecin is a well-characterized apoptosis inducing agent and often used as positive control [ 43 , 44 ]. Furthermore, heat shock treatment is a widely-used control method since eukaryotic cells form misfolded or aggregated proteins in the presence of thermal insults, thus inducing apoptosis [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of HSP70 is a feature of N-terminal ATPase HSP90 inhibitors and is regarded as a biomarker of drug activity [ 24 ]. Some have suggested that this HSP70 overexpression may allow cells to overcome the effects of N-terminal ATPase HSP90 inhibitor drugs when used as monotherapy in clinical trials [ 25 ].…”
Section: Introductionmentioning
confidence: 99%